Multiple cysticercus nodules in skin and brain in a Balinese woman: A case report (Medical Journal of Indonesia, 2002)
A case of multiple subcutaneous and cerebral cysticercosis in a 33-year-old Balinese female, is reported. The patient suffered from seizures since adolescence, which was not treated. Since three years before admission she started developing multiple nodules in the skin, starting from her forehead and since a year ago also in other parts of the head and body such as shoulders, chest and back. Serum sample tested against cysticercus antigen by immunoblot assay against antigen of Taenia solium was positive. The copro-antigen test was also positive, indicating the presence of the adult worm in the intestines. The patient was treated with praziquantel for the adult T. solium infection and thereafter with albendazole for the larval stages, which resulted in obvious reduction of the cerebral cysts and most of the subcutaneous nodules disappeared. However the adult worm was not recovered in the 24 hours stool specimen and after one year the immunoblot test was still positive. (Med J Indones 2002; 11: 169-73) Keywords: cysticercosis, Taenia solium, praziquantel, albendazole